Respuesta :
The solution is x=-1 and x=5. Why? Well like the question states you just have to substitute each number for x.
((-1)-3)^2+2((-1)-3)-8=0
16+(-8)-8=0
0=0
((5)-3)^2+2((-1)-3)-8=0
4+4-8=0
0=0
Each one is true. Hope this helped! :)
((-1)-3)^2+2((-1)-3)-8=0
16+(-8)-8=0
0=0
((5)-3)^2+2((-1)-3)-8=0
4+4-8=0
0=0
Each one is true. Hope this helped! :)
The value of x from the given expression is 1 and -5: Option A is correct.
Given the quadratic expression
[tex](x - 3)^2 + 2(x - 3) - 8 = 0[/tex]
Expand the expression
[tex](x - 3)^2 + 2(x - 3) - 8 = 0\\x^2-6x+9+2x-6-8=0\\x^2-6x+2x+9-6-8=0\\x^2-4x-5=0[/tex]
Factorize the result
[tex]x^2-4x-5=0\\x^2+5x-x-5=0\\x(x+5)-1(x+5) =0\\x-1=0 \ and \ x+5 =0\\x=1 \ and \ x = -5\\[/tex]
Hence the value of x is 1 and -5
Learn more here: https://brainly.com/question/11909547